2020
DOI: 10.1111/ctr.13832
|View full text |Cite
|
Sign up to set email alerts
|

Organ donation and transplant: The Islamic perspective

Abstract: Islam is the second most practiced religion globally, and the number of Muslims in Western countries has been increasing due to recent trends in migration. Studies have shown that Muslims in the Western world have more negative attitudes toward organ donation and transplantation compared with individuals from other religious backgrounds. Multiple barriers have been postulated that may prevent Muslims from exploring organ donation or transplantation. We conducted a literature review with the goal of summarizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 81 publications
0
36
0
Order By: Relevance
“…On a theoretical level, a great deal has been written about trust and organ donation. 24,[28][29][30] Perverse financial incentives, perceptions of economic gain, reports of transplant practices favouring the wealthy, manipulation of transplant systems in favour of certain patients and unethical procurement practices have all directly diminished public trust in organ transplantation.…”
Section: Transparency and Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…On a theoretical level, a great deal has been written about trust and organ donation. 24,[28][29][30] Perverse financial incentives, perceptions of economic gain, reports of transplant practices favouring the wealthy, manipulation of transplant systems in favour of certain patients and unethical procurement practices have all directly diminished public trust in organ transplantation.…”
Section: Transparency and Trustmentioning
confidence: 99%
“…The reasons for this include concerns about the sanctity of the body and sometimes contradictory positions taken in Islamic scripture and by some Islamic religious leaders. 10 , 24 , 25 The Singaporean organ donation system is telling for its flexibility, and the way in which it has had to adapt to balance accommodating the religious practices of some of its population with the ever-increasing demand for donor organs. The elasticity of organ donation policies in Singapore suggests that there is substantial governmental involvement and interest in providing a comprehensive and responsive transplant service.…”
Section: The Current State Of Play – Recent Statistics and Analysis Of Primary Trends Across Selected Countriesmentioning
confidence: 99%
“…Similar low rates of consent have been reported among ethnic minority families in the UK, namely 33%, compared with 61% among white donors [10]. In this regard, a recent review on the Islamic perspective on organ donation and transplantation reported that Muslims from a number of countries, including Spain, Poland, South Africa, the UK, and the USA, were more reluctant to donate their organs compared with adherents of other faiths [11]. The authors identified religious obstacles as being a central consideration in Muslim decisionmaking.…”
Section: Discussionmentioning
confidence: 67%
“…In the teaching, we see how the teacher introduces an internal religious argument against female genital mutilation because, according to (her interpretation of) Muslim religious rules, one must be buried with one's entire body, whereas female genital mutilation contravenes this rule. There is an ongoing debate among Muslim theologians and now many, for example, accept donations of organs (Ali et al 2020) which means that there are different views on the interpretations of the rule to bury the entire body. Nevertheless, female genital mutilation is taught in a directive way, and that there are religious proponents for this tradition is not considered in the classroom discussion.…”
Section: Female Genital Mutilationmentioning
confidence: 99%